Effects of modernization of the water treatment system in a selected swimming pool - Wyczarska-Kokot, Joanna; Dudziak, Mariusz; Lempart, Anna (Oficyna Wydawnicza Politechniki Wrocławskiej, 2019)
Based on the analysis of the modernization activities of the pool water treatment technology in a selected indoor swimming pool, the results of water quality improvement have been presented. The analysis of water quality parameters, operating parameters and in-house research that has been carried out in this pool for many years allowed us to evaluate the effects of modernization on water quality improvement, with special consideration of chloramine content in pool water (as a disinfection by product). The results of the research have been analyzed in terms of the current sanitary and hygienic guidelines for swimming pools.
Environment Protection Engineering. Vol. 45, 2019, nr 1, s. 31-43
Keywords: ochrona środowiska; inżynieria środowiska